Improving the Consistency of Nanoscale Etching for Atomic Force Microscopy Tomography Applications - Buckwell, Mark; Ng, Wing H.; Hudziak, Stephen; Mehonic, Adnan; Lanza, Mario; Kenyon, Anthony J. (Frontiers in Materials, 2019)
The atomic force microscope empowers research into nanoscale structural and functional material properties. Recently, the scope of application has broadened with the arrival of conductance tomography, a technique for mapping current in three-dimensions in electronic devices by gradually removing sample material with the scanning probe. This technique has been valuable in studying resistance switching memories and solar cells, although its broader use has been hindered by a lack of understanding of its reliability and practicality. Implementation can be preclusive, owing to difficulties in characterizing tip-sample interactions and accounting for probe degradation, both of which are crucial factors in process efficacy. This work follows the existing conductance tomography literature, presenting an insight into the repeatability and reliability of the material removal processes. The consistency of processes on a hard oxide and a softer metal are investigated, to understand the critical differences in etching behavior that might affect tomography measurements on heterostructures. Individual probe behavior stabilizes following a wearing-in stage and etching processes are consistent between probes, in particular on oxide. However, process inconsistency increases with applied force on metal. The effects of scan angle, tip speed and feedback gain are therefore explored and their tuning found to improve the spatial consistency of material removal. With these findings, we aim to present a critical study of the implementation of tomography with the atomic force microscope in order to contribute to its methodological development.